PENGARUH MEDIA TANAM SERBUK TANDAN KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN PENAMBAHAN KAPUR DOLOMID TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleorotus ostreatus L.) - ARIF, NAJMI; FIFENDY, MADES; RIZKI, RIZKI (Pendidikan Biologi, 2014)
ABSTRACTÂ White Oyster mushroom is kinds of wood mushroom. In cultivation it, generally the society used hay and sawdust as media plant. In West Pasaman the media plant difficulties get. So, require to find another alternative media that is using empty bunch of oil palm which not yet been exploited optimally by society. Chalk addition used for setting the plant pH media to approach neutral situation. This research have been done in August 2013 until January 2014 in Padang. This Research used Experimental method and Complete Random Device (RAL) in 5 treatment chalk heavy of dolomid and 4 times repetition, is : A0: 0 gr/baglog, A1: 7,5 gr/baglog, A2: 15 gr/baglog, A3: 22,5 gr/baglog, A4:30 gr/baglog. The heavy of oil palm bunch that used is about 500gr/baglog. Based on this research, got result that giving chalk of dolomid at media of oil palm bunch can improve white oyster mushroom production and growth. The average of long spreading miselium quickest about 24 day at A2 treatment, the average of most fruiting body 14,80 at A3 treatment, wet heavy average of fruit body 68 gram at A3 treatment of and the diameter of fruiting body cover highest were 8,58 cm at A1 treatment.Â